Young Raw Matters Ambassadors: High School Students Act as Science Communicators - Canino, Mariaconcetta; Zanelli, Alberto; Seri, Mirko; Degli Esposti, Alessandra; Torreggiani, Armida (Frontiers in Education, 2021)
Nowadays communication skills are essential for the successful future career of undergraduate students, as well as to develop a mindset able to face new challenges linked to a sustainable development and to adopt sustainable strategies with respect to finite resources on earth allowing the transition to the circular economy (CE) model. Here we present the experience of seven classes of teenagers involved in learning paths linked to researches in the field of material science aiming at developing more sustainable materials. The expected output was oriented toward the common goal of creating a communication tool targeting an external audience. The paths were proposed as a work-based experience in the framework of Raw Matters Ambassadors at Schools (RM@Schools), a European project which aims at raising awareness on the sustainable use of raw materials as well as increasing the interest for STEM disciplines, able to allow the future transition towards a low carbon society. By using a combination of approaches such as open discussion, learning by doing, and peer-to-peer education, students are involved in an experiential learning process to develop communication competencies and increase their awareness about sustainability development.